Transcutaneous electrical nerve stimulation as an adjuvant treatment for thoracolumbar acute hyperesthesia in chondrodystrophic dogs: a prospective blinded controlled clinical study - Gouveia, Débora; Cardoso, Ana; Carvalho, Carla; Moisés, Marina; Coelho, André; Balça, Maria Manuel; Alvites, Rui; Maurício, Ana Colette; Ferreira, António; Martins, Ângela (Frontiers in Pain Research, 2025)
IntroductionAcute paraspinal hyperesthesia in dogs can result in a combination of nociceptive and neuropathic pain, often requiring pharmacological intervention. However, non-pharmacologic approaches, such as two-channel transcutaneous electrical nerve stimulation (TENS), may also be beneficial. Evidence from human medicine suggests that conventional TENS reduces pain scores and potentially decreases the need for analgesic medication. This study aimed to evaluate the efficacy of TENS as an adjunctive treatment for thoracolumbar paraspinal hyperesthesia in dogs.MethodsThis prospective, blinded, controlled cohort study was conducted in a clinical setting. Dogs diagnosed with paraspinal hyperesthesia, classified as grade 4 or 5 on the modified Frankel scale (MFS) and with a dynamic interactive visual analog scale (DIVAS) score ≥14, were included. The subjects were randomized into two groups: the study group (SG), which received standard pharmacological protocol (PSP) plus TENS, and the control group (CG), which received PSP only. Observers blinded to treatment allocation scored video recordings of the dogs. Assessments were performed every 24 hours from T0 (admission) to T8, with evaluations in SG occurring 5 minutes before each TENS session.ResultsA total of 818 dogs were enrolled, with 605 (74%) in the SG and 213 (26%) in the CG. In the first 48 hours, SG demonstrated a faster reduction in muscle tone compared to CG. While all dogs transitioned from a hyperesthetic to a non-painful state, SG showed a significantly faster recovery from T2 (48 h) to T4. A significant difference was observed between groups in DIVAS scores (p < 0.001). Additionally, SG had a shorter mean hospital stay (2.14 days) compared to CG, which required twice as long (p < 0.001).DiscussionThese findings suggest that TENS may be an effective adjunctive therapy for managing acute thoracolumbar hyperesthesia in dogs, promoting early recovery by reducing pain, medication dependency, and hospitalization duration. However, the study's reliance on subjective assessments presents a limitation, potentially introducing bias. Further research with objective outcome measures is necessary to validate these findings and optimize the integration of TENS in veterinary pain management protocols.